2020
DOI: 10.1016/j.diabres.2020.108374
|View full text |Cite
|
Sign up to set email alerts
|

Newly-diagnosed diabetes and admission hyperglycemia predict COVID-19 severity by aggravating respiratory deterioration

Abstract: We investigated whether pre-existing diabetes, newly-diagnosed diabetes, and admission hyperglycemia were associated with COVID-19 severity independently from confounders. Methods: We retrospectively analyzed data on patients with COVID-19 hospitalized between February and April 2020 in an outbreak hospital in NorthEast Italy. Pre-existing diabetes was defined by self-reported history, electronic medical records, or ongoing medications. Newly-diagnosed diabetes was defined by HbA1c and fasting glucose. The pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
168
4
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(222 citation statements)
references
References 36 publications
19
168
4
8
Order By: Relevance
“…Furthermore, we discovered that the smallersized studies yielded excessively wide CIs as compared to larger studies (Table 1). Nonetheless, sensitivity analysis suggested that these small studies did not contribute much to the pooled estimate as our findings remained consistent, except when Fadini et al [36] or Chang et al [38] were excluded, which exaggerated the pooled estimates (Appendix Figure S2B). We detected asymmetry in the funnel plot which was further ascertained by Egger's test (P<0.001; Appendix Figure S3), although Begg's test indicated otherwise (P=0.245), suggesting the presence of publication bias.…”
Section: Fasting Blood Glucosementioning
confidence: 52%
See 1 more Smart Citation
“…Furthermore, we discovered that the smallersized studies yielded excessively wide CIs as compared to larger studies (Table 1). Nonetheless, sensitivity analysis suggested that these small studies did not contribute much to the pooled estimate as our findings remained consistent, except when Fadini et al [36] or Chang et al [38] were excluded, which exaggerated the pooled estimates (Appendix Figure S2B). We detected asymmetry in the funnel plot which was further ascertained by Egger's test (P<0.001; Appendix Figure S3), although Begg's test indicated otherwise (P=0.245), suggesting the presence of publication bias.…”
Section: Fasting Blood Glucosementioning
confidence: 52%
“…However, we were unable to establish firm evidence as the observed heterogeneity remained unexplained (see footnote in Table 1) and the observed effects were diminished following the exclusion of Fadini et al [36] or Li et al [35] (Appendix Figure S2A). In DRMA comprising of two studies [36,37], we failed to observe exposureresponse gradient (RR 1.23 [95% CI: 0.90-1.68]; P heterogeneity =0.008; Figure 4A), although studyspecific slopes indicated that such trend exists. Considering this, we deemed the quality of evidence to be moderate for qualitative assessment and low for quantitative assessment.…”
Section: Fasting Blood Glucosementioning
confidence: 85%
“…Notably, Li et al [13] at a mean followup of 30 days reported nearly 2-fold higher risk of all-cause death in individuals with new-onset diabetes (HR 9.42; 95% CI, 2.18-40.7), in comparison to pre-existing diabetes (HR 4.63; 95% CI 1.02-21.0) vs. normoglycemic people with COVID-19. Coincidentally, Fadini et al [18] also found a stronger association in increase (p = 0.004) in ICU admission or death in people with new-onset diabetes (RR 3.06; 95% CI, 2.04-4.57), compared with pre-existing diabetes (RR 1.55, 95% C.I. 1.06-2.27) vs. normoglycemic patients with COVID-19, in unadjusted analysis.…”
Section: Outcomes In Patients With New-onset Diabetes Versus Pre-exismentioning
confidence: 90%
“…into worse outcomes. Worsening respiratory function is believed to be the major factor responsible for the detrimental effect of hyperglycemia in patients infected by SARS-CoV-2 [8]. It has been observed that there exist varying magnitudes of association between fasting blood glucose levels and severe/critical COVID-19 illness among patients presenting with hyperglycemia without a known diagnosis of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that every 2 mmol/L (36 mg/dL) increase in fasting plasma glucose levels correlates with increasing COVID-19 severity in both diabetics and non-diabetics, but the association was stronger among the latter [8]. Furthermore, the optimal fasting blood glucose levels for predicting critical COVID-19 illness were reported to be ≥ 6.50 mmol/L [9].…”
Section: Disease Severity and Complicationsmentioning
confidence: 99%